220k views
3 votes
Use the remainder theorem to find the value of F(x).
2. Find F(-2).
F(x)=4x^3-2x^2+3x-2

User Thuan
by
6.3k points

1 Answer

2 votes

we can do the same here as you saw before, but using long division to check the remainder, hmmm so f(-2), meaning x = -2 for an expression of x + 2 = 0, so let's firstly divide f(x) by x + 2 using long division, will be the same as synthetic, but just to check, then we'll see what f(-2) is.

Check the picture below.

f(-2) = 4(-2)³ - 2(-2)² +3(-2) - 2

f(-2) = -48

Use the remainder theorem to find the value of F(x). 2. Find F(-2). F(x)=4x^3-2x^2+3x-example-1
User David Tobiano
by
5.7k points